Determination of physical properties and viability in different colors of Pueraria seeds - Araújo, Ádamo De Souza; Pinheiro, Romário de Mesquita; da Silva, Elson Junior Souza; Gadotti, Gizele Ingrid; Monteiro, Rita de Cassia Mota; Bernardy, Ruan (Revista Agrogeoambiental, 2022)
The differences observed in the physical properties of the seeds may indicate types of equipment for harvesting and processing, in addition to variability between plants. It was studied the characterization of the dimensions of the seeds, linear and geometric and the viability defined in categories. The results showed that the studied seeds did not reach a spherical shape, and their mass underwent variation resulting from the sorption and desorption process. The morphological characteristics suggested slight differences in the shape of the seeds. A high coefficient of variation was observed for fresh seed mass (18.34%), volume index (18.07%), seed volume (18.07%), and seed surface area (12.47%). Seed colorations showed differences in germination. The analysis concluded that all categories of seeds are viable. These descriptive data indicate that the combination of seed characteristics and the germination process help in methodologies for planting, harvesting, processing, and storage of seeds.